The sociology of late secularization: social divisions and religiosity. (22nd September 2016) - Bruce, Steve
Abstract: At the start of the twentieth century the religious differed from the religiously indifferent largely in being religious. Now they differ in a number of other social and demographic characteristics that reduce interaction between the two populations further than simple numbers would require. That some of the main carriers of religion are immigrants or adherents of recently imported faiths reinforces the sense that religion is what other people do. In the context of the stock of religious knowledge being depleted and religion‐taken‐too‐seriously being unpopular, the narrow demographic base of the religious makes conversion unlikely and thus makes the reversal of secularization unlikely.